2007
DOI: 10.1614/wt-06-130.1
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Herbicides in U.S. Crop Production

Abstract: The vast majority of crop hectares in the United States are treated with chemical herbicides annually. The adoption of herbicides for weed control was rapid in the 1950s and 1960s. Herbicides replaced the use of millions of workers to pull and hoe weeds by hand and greatly reduced the use of tillage for weed control. Costs of production were reduced and crop yields increased because herbicides were cheaper and more effective than hand weeding and cultivation. Organic crop growers cite weed control as their gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
179
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(199 citation statements)
references
References 14 publications
0
179
0
3
Order By: Relevance
“…This is could be due to their ability to re-germinate promptly from vegetative reproductive structures such as rhizomes or tubers, especially if these structures are dispersed through the field upon cultivation in too wet soil conditions [15]. Moreover, hilling is not effective against weeds within the crop row.…”
Section: Effect On Weed Growthmentioning
confidence: 99%
“…This is could be due to their ability to re-germinate promptly from vegetative reproductive structures such as rhizomes or tubers, especially if these structures are dispersed through the field upon cultivation in too wet soil conditions [15]. Moreover, hilling is not effective against weeds within the crop row.…”
Section: Effect On Weed Growthmentioning
confidence: 99%
“…Growers of organic crops cite weed control as their greatest difficulty in crop production because they are not permitted to use chemical herbicides (Gianessi & Reigner (2007). They substitute hand weeding and cultivation for herbicides at a greatly increased cost and with reduced effectiveness.…”
Section: The Costs Of Weed Control In Organic Farming Are More Expensivementioning
confidence: 99%
“…In addition, organic crop growers were unwilling to accept hoeing damage to their vegetable crops and to increase plants spacing because of yields losses. Also, the method is highly expensive if enough labor is used to remove weeds: corn required 150 h ha -1 , cotton 165 h ha -1 , and spinach 516 h ha -1 (Gianessi & Reigner, 2007). Chicouene (2007) have summarized the reviews about mechanical weeding and reported that mechanical weeding is certainly the most immediately applicable method for weed management when using chemicals is undesirable.…”
Section: Mechanical Weedingmentioning
confidence: 99%
See 2 more Smart Citations